Species Diversity, Host Association, and Evolutionary History of Cronartium: An Important Global Fungal Pathogen to Trees - Jingyu Zhang; Clement K. M. Tsui; Chongjuan You (Ecology and Evolution)
ABSTRACT Pine stem rust, the most damaging and widespread forest disease occurring in pine trees in the Northern Hemisphere, is primarily caused by Cronartium species (Pucciniales, Melampsorineae). While the phylogenetic relationships of major Cronartium species have been largely elucidated, there is limited understanding of their species diversity and the evolutionary processes shaping their distribution patterns. In this work, we performed broad sampling and sequencing of Cronartium taxa in China together with additional sequence data and other accessions in NCBI to investigate the diversification and to estimate the divergence time of major evolutionary events in this genus. Molecular dating analysis suggested that the divergence of the genus Cronartium probably was around 91.78 Ma during the Upper Cretaceous. It is believed that Cronartium species may have originated in Asia and North America, with intercontinental dispersals occurring primarily during the Middle Eocene, Middle Miocene, and Pliocene. These dispersal events likely took place through the North Atlantic Land Bridge, the De Geer Route, and the Bering Land Bridge, and subsequently diverged through sporadic dispersal and vicariance events. Furthermore, our analysis of host associations revealed that the diversification of Cronartium species was correlated with their telial‐hosts, and some species may have experienced host jump events, indicating a complex interplay between host specificity and pathogen–host interaction during Cronartium evolution.